1998
DOI: 10.1097/00005053-199803000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neuropsychiatric Effects of Malaria in Ghana

Abstract: This study investigated the long-term emotional and cognitive effects of malaria infection in a sample of community resident nonmigratory Ghanaian adults, comparing 142 individuals with a documented history of clinical falciparum malaria and 30 controls without a lifetime medical diagnosis of malaria. Results were based on self-report inventory and interview-based approaches to assessment of emotional status as well as individual administration of the Mini-Mental State Examination. Our findings indicated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…In adults, the incidence of neurological and cognitive impairment is lesser than in children ( ! 5%), but the range of types of sequelae is much greater, including cranial nerve lesions, neuropathies, extrapyramidal disorders, focal epilepsy, poor dichotic listening, personality change, depression, and subclinical mixed anxiety-depression syndrome [112][113][114] .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In adults, the incidence of neurological and cognitive impairment is lesser than in children ( ! 5%), but the range of types of sequelae is much greater, including cranial nerve lesions, neuropathies, extrapyramidal disorders, focal epilepsy, poor dichotic listening, personality change, depression, and subclinical mixed anxiety-depression syndrome [112][113][114] .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In previous studies of child intelligence and learning in LMIC, cognitive development after disease is a prevalent theme, with research exploring the effects of HIV/AIDS [2831] and malaria [3240] on the abilities and achievement of children in African countries. Investigators in these studies often use instruments developed in high income countries; and, for the most part, the strategies have been successful in demonstrating a hypothesized compromise in cognitive development due to disease effects on the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few reports of neurologic sequelae in adults [8, 9, 10]. Neuropsychiatric disorders following falciparum malaria were also described in 19 adults and 3 children in a large prospective Vietnamese study, and were referred to as a ‘post-malaria neurological syndrome’ [14].…”
Section: Discussionmentioning
confidence: 99%
“…The neuropsychological disorders may be explained by diffuse damage of the deep white matter tracts, possibly leading to dysfunction of the memory circuits and other cortical pathways. Dugbartey et al [9]found a persistent subclinical anxiety-depression syndrome after falciparum malaria in a group of 142 Ghanaian patients compared with a control group. Varney et al [8]reported personality changes and depression in Vietnam veterans who had had cerebral malaria in comparison with a control group who had not had malaria, 25 years after the war.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation